ANALISIS PERBANDINGAN KINERJA KEUANGAN PEMERINTAH DAERAH KOTA SURAKARTA SEBELUM DAN PADA MASA JABATAN GIBRAN RAKABUMING RAKA MENGGUNAKAN PENDEKATAN RASIO KEUANGAN - Ichlasul Amal Akuba; Darmawati; Andi Kusumawati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This research aims to determine the Financial Performance of the City of Surakarta before and during Gibran Rakabuming Raka's term of office. This research is quantitative descriptive research, namely research that attempts to explain the solution of current problems using numbers, starting from data collection, interpretation of the data and the appearance of the results. The data collection technique used in this research uses documentation techniques. The data used is secondary data in the form of the Surakarta City Regional Revenue and Expenditure Budget Realization Report for 2018-2023. The results of this research are 1) The Independence Ratio of Surakarta City before and during the government of Gibran Rakabuming Raka, generally said to be Ineffective. 2) The Efficient Ratio of Surakarta City before Gibran's administration on average could be said to be Less Efficient, whereas during Gibran's administration on average it could be said to be Inefficient. 3) The Effectiveness Ratio of the City of Surakarta before Gibran's administration on average could be said to be Very Effective, whereas during Gibran's administration on average it could be said to be Quite Effective. 4) The Growth Ratio of Surakarta City during the Gibran administration can be said to be on average better than the Growth Ratio before the Gibran administration